Presumed cytomegalovirus retinitis late after kidney transplant - Silva,Filipa (2021)
Abstract Cytomegalovirus (CMV) retinitis is a rare manifestation of CMV invasive disease and potentially threatening to vision in immunocompromised individuals. Clinical suspicion is fundamental since it is an unusual entity with a progressive and often asymptomatic installation over a long period. The authors report a 70-year-old man with diabetic nephropathy who underwent a kidney transplant (KT) in August 2014 with good clinical evolution. No previous CMV infection or episodes of acute rejection were reported. Five years after transplant, he was admitted due to a reduced visual acuity of the left eye with seven days of evolution with associated hyperemia, without exudate. The ophthalmologic evaluation was compatible with acute necrosis of the retina and presumed associated with CMV infection. He had a progressive improvement after ganciclovir initiation. CMV retinitis is one of the most serious ocular complications in immune-suppressed individuals and can lead to irreversible blindness, and because of that, early diagnosis and treatment remains crucial in obtaining the best visual prognosis in affected patients. Secondary prophylaxis with ganciclovir is not consensual, neither is the safety of reintroducing the antimetabolite in these cases.